Vive la Paris - Codell, Esmé Raji, 1968- (Hyperion Paperbacks for Children, 2007)
Fifth-grader Paris learns some lessons about dealing with bullies of all kinds as she wonders how to stop a classmate from beating up her brother at school and as she learns about the Holocaust from her piano teacher, Mrs. Rosen.